Misreading or living in denial? Reindeer overstocking and long‐term effects on vegetation: An experimental approach - Bård‐Jørgen Bårdsen; Hans Tømmervik; Marius Warg Næss; Jarle Werner Bjerke (Ecosphere)
Abstract In an era marked by accelerating climate change, habitat loss, and shifting land use patterns, it is crucial to understand the intricate effects of multiple stressors on ecosystems. This long‐term study sheds light on the complex interplay between grazing and habitat characteristics on pasture dynamics and offers insights into how various stressors affect ecosystems facing environmental challenges. Our experimental study documents that manipulation in restricting reindeer grazing and trampling through fencing led to higher ground‐lichen biomass, volume, height (particularly in one habitat), and cover compared with open‐control plots. The effect of fencing varied depending on habitat, and for lichen biomass, volume, and height, the lowest values were observed in windswept exposed ridges and mountain heaths (exposed/mountain), and the highest values were observed in forested and leeward‐heath (forest/leeward) habitat. The average (past five years) number of reindeer per square kilometer had indirect effects that varied across habitats. We observed negative density dependence in the open plots for height in the exposed/mountain habitats. Fencing reduced this effect, which was also valid for biomass except that habitat did not affect the effect of density. Surprisingly, in the forest/leeward areas, the estimated effects of reindeer density on biomass, volume, and height were positive for the fenced plots. Negative density dependence was evident for lichen cover irrespective of habitats and manipulation, even though this effect had little biological significance, whereas cover at the initiation of the experiment positively affected later recordings (particularly for the controls). Our models showed high explanatory power, highlighting the significance of reindeer density and habitat as predictors of ground‐lichen dynamics. Overall, negative density‐dependent effects were observed in the open plots in the most exposed areas, and fencing mitigated the negative impact of reindeer on lichens, particularly in less exposed areas. We challenge the “equilibrium” and “nonequilibrium” frameworks for explaining livestock‐pasture dynamics. We propose future studies to estimate the relative importance of density‐dependent and density‐independent factors, such as climate, using models considering both mechanisms simultaneously.